Single-nucleus transcriptome profiling of prefrontal cortex induced by chronic methamphetamine treatment - Yi Li; Yong Wu; Rong Liu; Xuan Yu; Xiaochuan Wang; Zhen Wei; Kuan Zeng; Jianzhi Wang (General Psychiatry, 2023)
Background Methamphetamine (METH) addiction causes a huge burden on society. The prefrontal cortex (PFC), associated with emotion and cognitive behaviours, is also involved in addiction neurocircuitry. Although bulk RNA sequencing has shown METH-induced gene alterations in the mouse PFC, the impact on different cell types remains unknown.Aims To clarify the effects of METH treatment on different cell types of the PFC and the potential pathways involved in METH-related disorders.Methods We performed single-nucleus RNA sequencing (snRNA-seq) to examine the transcriptomes of 20 465 nuclei isolated from the PFC of chronic METH-treated and control mice. Main cell types and differentially expressed genes (DEGs) were identified and confirmed by RNA fluorescence in situ hybridization(FISH).Results Six main cell types were identified depending on the single-cell nucleus sequencing; of particular interest were the mature oligodendrocytes in the PFC. The DEGs of mature oligodendrocytes were enriched in the myelin sheath, adenosine triphosphate (ATP) metabolic process, mitochondrial function and components, and so on. The messenger RNA levels of Aldoc and Atp5l (FISH) and the protein level of the mitochondrial membrane pore subunit TOM40 (immunofluorescence) decreased in the mature oligodendrocytes. Fast blue staining and transmission electron microscopy image indicated myelin damage, and the myelin thickness decreased in METH brains.Conclusions snRNA-seq reveals altered transcriptomes of different cell types in mouse PFC induced by chronic METH treatment, underscoring potential relationships with psychiatric disorders.